Le donne ostrogote in Italia e i loro nomi - Nicoletta Francovich Onesti (Filologia Germanica)
The article gathers all known Gothic feminine personal names recorded in historical sources from Ostrogothic Italy. The paper first analyzes in what type of written sources in particular do we find women’s names, what was their role and position in history, and when possible investigates their status and religion, together with their family links, genealogies and relations. Then the article goes on to examine the linguistic and onomastic characters of such names, which enables us to trace a few peculiarities occurring in the names of the royal family, since women belonging to Amal dynasty all have particularly solemn and old-fashioned Gothic compounded names.